Benzotiadiazole (BTH) na indução de resistência do feijão-de-corda [Vigna unguiculata (L.) Walp.] ao nematóide Meloidogyne incognita, raça 1 - Miranda, Aparecida Simone Martins (2007)
Cowpea it is an economically important leguminous to several countries around world, including Africa and Brazil, the two major producers. Cowpea's breeding, however, is considerably hampered by pathogen, like nematodes and pests [...]